Federal accounting handbook policies, standards, procedures, practices - Tierney, Cornelius (John Wiley & Sons, 2000)
"For the first time in decades, federal accounting practices have been altered by significant changes imposed by Congress and regulatory agencies, as well as by the establishment in 1990 of the Federal Accounting Standards Advisory Board (FASB). Written in nontechnical language for both the professional and nonprofessional, Wiley Federal Accounting Handbook provides all you need to know about the what, why, when, and how of federal financial management."--BOOK JACKET.